2018
DOI: 10.1002/pmic.201700444
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Protein Interaction Network Analysis Identifies Shared and Distinct Functions for the Human ROCO Proteins

Abstract: Signal transduction cascades governed by kinases and GTPases are a critical component of the command and control of cellular processes, with the precise outcome partly determined by direct protein–protein interactions (PPIs). Here, we use the human ROCO proteins as a model for investigating PPI signaling events—taking advantage of the unique dual kinase/GTPase activities and scaffolding properties of these multidomain proteins. PPI networks are reported that encompass the human ROCO proteins, developed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 77 publications
(65 reference statements)
4
43
0
Order By: Relevance
“…This scaffolding capacity provides LRRK2 with the flexibility to interact with a wide range of proteins -and thereby the potential to regulate distinct processes within the cell (Good et al 2011;Garbett & Bretscher, 2014). An insight into the potential complexity that this opens up is provided by examining the protein interactome for LRRK2, where over 100 protein interactors have been reported in the literature Tomkins et al 2018). While a proportion of these are likely to be false positives, the functional diversity of these interactions supports…”
Section: Molecular Pleiotropymentioning
confidence: 99%
See 1 more Smart Citation
“…This scaffolding capacity provides LRRK2 with the flexibility to interact with a wide range of proteins -and thereby the potential to regulate distinct processes within the cell (Good et al 2011;Garbett & Bretscher, 2014). An insight into the potential complexity that this opens up is provided by examining the protein interactome for LRRK2, where over 100 protein interactors have been reported in the literature Tomkins et al 2018). While a proportion of these are likely to be false positives, the functional diversity of these interactions supports…”
Section: Molecular Pleiotropymentioning
confidence: 99%
“…; Tomkins et al . ). While a proportion of these are likely to be false positives, the functional diversity of these interactions supports a pleiotropic role for the multitude of complexes that LRRK2 is likely to form based upon these data, although it is noteworthy that our understanding of the complexes formed and co‐ordinated by LRRK2 is still in its infancy.…”
Section: Introductionmentioning
confidence: 97%
“…A single amino-acid change, G2019S, increases LRRK2 kinase activity (1), leading to a toxic cascade that kills dopaminergic neurons, but the main steps in this pathological signalling pathway remain to be determined. A number of studies highlighted a diverse range of >30 proteins that might be phosphorylated by LRRK2, suggesting it is a generalised kinase (2). However, several research teams have recently reported that LRRK2 is a more specific kinase, phosphorylating Rab GTPases (3)(4)(5)(6)(7)(8).…”
Section: Significance Statementmentioning
confidence: 99%
“…This support shedding light on communal pathways involving proteins of interest (810). Additionally, literature extracted PPI data can support the prioritization of interactions from high-throughput experiments (which generate large lists of potential PPI hits), assisting the selection of candidates for further analysis/validation (11).…”
Section: Introductionmentioning
confidence: 99%